2019
DOI: 10.3390/rs11020169
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Landsat-8 OLI Atmospheric Correction Algorithms for Inland Waters

Abstract: The OLI (Operational Land Imager) sensor on Landsat-8 has the potential to meet the requirements of remote sensing of water color. However, the optical properties of inland waters are more complex than those of oceanic waters, and inland atmospheric correction presents additional challenges. We examined the performance of atmospheric correction (AC) methods for remote sensing over three highly turbid or hypereutrophic inland waters in China: Lake Hongze, Lake Chaohu, and Lake Taihu. Four water-AC algorithms (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 70 publications
(80 reference statements)
3
34
0
2
Order By: Relevance
“…This study has identified Acolite SWIR AC algorithm as the most appropriate algorithm to retrieve Rhow in the green and red bands. Similar results were obtained in the inland waters of China, where Acolite SWIR and Acolite DSF provided better results compared with other tested AC algorithms [35]. These assessment results showed the Acolite SWIR and Acolite DSF algorithms can be effectively applied in turbid waters, while they perform poorly in clear waters.…”
Section: L8-olisupporting
confidence: 76%
See 2 more Smart Citations
“…This study has identified Acolite SWIR AC algorithm as the most appropriate algorithm to retrieve Rhow in the green and red bands. Similar results were obtained in the inland waters of China, where Acolite SWIR and Acolite DSF provided better results compared with other tested AC algorithms [35]. These assessment results showed the Acolite SWIR and Acolite DSF algorithms can be effectively applied in turbid waters, while they perform poorly in clear waters.…”
Section: L8-olisupporting
confidence: 76%
“…The performance of different AC algorithms for L8-OLI data recorded over moderately turbid to turbid waters have been reported by several studies [1,[32][33][34][35]. The study conducted by [32] has used Acolite AC algorithm to derive SPM concentrations over the coastal mud banks of French Guiana.…”
Section: L8-olimentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Maciel et al [79] obtained MAPE values of about 20% for turbid waters in the Amazon Floodplain lakes. Wang et al [87] also observed MAPE values of about 20% for 6SV atmospheric correction for green and red bands of OLI (Operational Land Imager) Landsat-8 over eutrophic environments of lakes in China. In the present work, the variability between in situ and satellite-derived R rs may have influenced satellite OHA validation results ( Figure 9B Another factor that may have affected OHA performance when applied to the image was that not all sampling stations were collected on the same day of the satellite overpass.…”
Section: Oha Framework Assessmentmentioning
confidence: 94%
“…The 6SV is an advanced radiative transfer code capable of accounting for radiation polarization in a mixed molecular-aerosol atmosphere being a vector version of the 6S [33]. The 6S atmospheric correction has already been successfully used in lakes and reservoirs [21,32,[34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%